ANSWER
![x = - 11\: or \: x = 3](https://tex.z-dn.net/?f=x%20%3D%20%20%20-%2011%5C%3A%20or%20%5C%3A%20x%20%3D%20%203)
EXPLANATION
The quadratic equation given to us is
![{x}^{2} + 8x = 33](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%2B%208x%20%3D%2033)
We add half the square of the coefficient of
![x](https://tex.z-dn.net/?f=x)
to both sides of the equation to obtain,
![{x}^{2} + 8x + {(4)}^{2} = 33 + {(4)}^{2}](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%2B%208x%20%2B%20%20%7B%284%29%7D%5E%7B2%7D%20%20%3D%2033%20%2B%20%20%7B%284%29%7D%5E%7B2%7D)
This implies that,
![{x}^{2} + 8x + {(4)}^{2} = 33 + 16](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%2B%208x%20%2B%20%20%7B%284%29%7D%5E%7B2%7D%20%20%3D%2033%20%2B%2016)
The right hand side simplifies to
![{x}^{2} + 8x + {(4)}^{2} = 49](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%2B%208x%20%2B%20%20%7B%284%29%7D%5E%7B2%7D%20%20%3D%2049)
The left hand side is a perfect square.
This gives us
![{(x + 4)}^{2} = 49](https://tex.z-dn.net/?f=%20%7B%28x%20%2B%204%29%7D%5E%7B2%7D%20%20%3D%2049)
We take the square root of both sides
![x + 4 = \pm \sqrt{49}](https://tex.z-dn.net/?f=x%20%2B%204%20%3D%20%20%5Cpm%20%5Csqrt%7B49%7D%20)
This evaluates to
![x + 4 = \pm 7](https://tex.z-dn.net/?f=x%20%2B%204%20%3D%20%20%5Cpm%207)
We make x the subject.
![x = - 4\pm 7](https://tex.z-dn.net/?f=x%20%3D%20%20%20-%204%5Cpm%207)
We now split the square root sign to get
.
![x = - 4 - 7 \: or \: x = - 4 + 7](https://tex.z-dn.net/?f=x%20%3D%20%20%20-%204%20-%207%20%5C%3A%20or%20%5C%3A%20x%20%3D%20%20-%204%20%2B%207)
![x = - 11\: or \: x = 3](https://tex.z-dn.net/?f=x%20%3D%20%20%20-%2011%5C%3A%20or%20%5C%3A%20x%20%3D%20%203)
The correct answer is A.